BRANDING INNOVATION FOR TRADITIONAL BEVERAGE PRODUCTS: INCREASING THE COMPETITIVENESS OF MSMES IN PENTINGSARI VILLAGE, SLEMAN, DIY YOGYAKARTA - Nova Yudha Andriansyah Putra; Gilang Fahreza; Syaharuddin, Syaharuddin; Claudia Dwi Martina; Izzat Habib; Astria Putri Ramadhani; Rifqi Muhammad Ihsan (Bajang Institute, 2025)
Pentingsari Village has significant potential in the agricultural sector, particularly in the availability of local food ingredients such as ginger, sappanwood, coffee, lemongrass, cloves, and cinnamon. However, this potential has not been fully utilized by the local population. Limited knowledge and skills in processing food ingredients into value-added products is one of the main challenges faced. This community service activity aims to improve the ability of the Pentingsari Village community to process local food ingredients into creative, economically valuable food products. The methods applied in this activity include identifying local food ingredients, providing counseling and inviting participants, and providing theoretical and practical training in food processing. This activity emphasizes the importance of clean processing, product innovation, and efficient marketing methods. This activity is expected to improve the community's skills and insight in food processing, while encouraging the development of competitive local products in the market. Through this training, it is hoped that there will be an increase in the income and welfare of Pentingsari Village residents, as well as strengthening the local economy by utilizing the potential of available natural resources. Evaluation of this program shows an increase in product quality and an entrepreneurial spirit among participants, which is expected to continue and bring long-term benefits to the village community.